Peningkatan Pengalaman Calon Wisatawan dengan Aplikasi Augmented Reality di Taman Hutan Raya Mangrove Ngurah Rai Bali dengan Metode RAD (Rapid Application Development) - Kadek Surya Adi Saputra; Wayan Andrika Putera; Ni Putu Jois Tika Dewi (Jurnal Teknologi Informasi dan Multimedia, 2024)
The advancement of technology today provides an opportunity to develop more effective media for information and promotion. One of the popular technologies is Augmented Reality (AR), which has the potential to offer interactive information and innovative promotion in the tourism sector. This study focuses on developing an AR application for the Ngurah Rai Mangrove Forest Park (Tahura) in Bali, which until now has been promoted conventionally with limited reach. This application is designed to enhance user experience in interacting with information related to tourism destinations through AR technology while also promoting Tahura Mangrove to a broader audience. The system was developed using the RAD (Rapid Application Development) method, which includes the following stages: 1) Requirements Planning, 2) System Design, 3) Development, and 4) Implementation. Blackbox testing was conducted to evaluate system functionality, while the System Usability Scale (SUS) test involving 30 participants assessed the user experience aspects of the application. The test results showed a SUS score of 76%, indicating a good level of acceptance and satisfaction. Additionally, there was a 74% increase in prospective tourists' understanding of the destination after using the application compared to before. With these results, the AR application for Ngurah Rai Mangrove Forest Park is expected to become an innovative medium to introduce mangrove ecotourism and increase public and tourist interest in visiting.